2015
DOI: 10.1370/afm.1797
|View full text |Cite
|
Sign up to set email alerts
|

Health IT-Enabled Care Coordination: A National Survey of Patient-Centered Medical Home Clinicians

Abstract: PURPOSE Health information technology (IT) offers promising tools for improving care coordination. We assessed the feasibility and acceptability of 6 proposed care coordination objectives for stage 3 of the Centers for Medicare and Medicaid Services electronic health record incentive program (Meaningful Use) related to referrals, notification of care from other facilities, patient clinical summaries, and patient dashboards. METHODSWe surveyed physician-owned and hospital/health system-affiliated primary care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…The inability to transfer clinical information between organizations remains a persistent barrier to care coordination, as evidenced by a recent decrease in the number of operational HIEs [9] and the challenges primary care practices face in using health IT to coordinate emergency and inpatient care [4]. Our findings seem to align with those of a prior qualitative study, in which consumers expressed willingness to make tradeoffs between privacy and security if a mobile health (mHealth) intervention offered increased convenience or benefits [23].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The inability to transfer clinical information between organizations remains a persistent barrier to care coordination, as evidenced by a recent decrease in the number of operational HIEs [9] and the challenges primary care practices face in using health IT to coordinate emergency and inpatient care [4]. Our findings seem to align with those of a prior qualitative study, in which consumers expressed willingness to make tradeoffs between privacy and security if a mobile health (mHealth) intervention offered increased convenience or benefits [23].…”
Section: Discussionsupporting
confidence: 74%
“…In many communities, such as large urban areas, care is fragmented across health systems and providers [3,4]. Resulting failures in care coordination can lead to adverse outcomes such as hospital readmissions [5] and wasteful health spending [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…116 Finally, care managers emerged as important facilitators of effective HIT use. Morton et al 120 found that practices with a non-clinician member of staff who was responsible for co-ordinating care were much better at care co-ordinating activities and conducting these activities electronically. Other studies 118 also noted that the care manager provided much-needed support to ensure smooth operations.…”
mentioning
confidence: 99%
“…3 In an analysis of response to health care delivery reforms, Sandy et al find that, among practices participating with a large commercial insurer, patientcentered medical home recognition seems to be positively associated with meeting quality benchmarks but negatively associated with efficiency parameters. 4 In their analysis, the authors ask, "Should a physician spend time and energy focusing on structural measures and process changes such as those embodied in NCQA [National Center for Quality Assurance] PCMH recognition?…”
mentioning
confidence: 99%